Síntese de catalisadores de níquel e rênio suportados em carvão ativado para a hidrogenação do furfural e do ácido levulínico - Abreu, Claudio Roberto Almeida de (2020)
This work evaluated the performance of nickel and rhenium catalysts supported on activated carbon in the hydrogenation of furfural (FAL) to furfuryl alcohol (FOL) and from levulinic acid (AL) to g-valerolactone (GVL). The catalysts were synthesized by wetness co-impregnation in order to obtain nominal content of 5% (w/w) Ni and 0; 0.5; 1; 2 or 5% (w/w) Re. For the characterization of the materials, it was used the techniques of physisorption of N2 at 77 K, X-ray diffraction, programmed temperature reduction, thermogravimetric analysis, and CO chemisorption. The catalytic tests were conducted in a batch reactor at different temperatures (60 150 ºC for FAL and 60-120 o C for AL) and H2 pressures (10-30 bar for FAL and 20-40 bar for AL) in aqueous phase. The formation of a Ni Re metal alloy was evidenced, since the addition of Re reduced the reducibility of Ni. There was an increase in metallic dispersion (10% to 18%) with an increase in the Re content, except for the 5% Re content (8%). In the hydrogenation of FAL, the catalysts with the best performances were 5%Ni-5%Re/C500 (conversion = 79%, selectivity = 91%) and 5%Ni-5%Re/C350 (conversion = 85%, selectivity = 97%). In the hydrogenation of AL, these catalysts also showed the best performance (conversion = 72%, selectivity = 97%). The calcination temperature proved to be an important parameter for the stability of the catalysts: after four reuse cycles, the catalyst 5%Ni-5%Re/C350 lost 60% of its activity in the conversion of the FAL and 53% in the conversion of the AL, while the 5%Ni-5%Re/C500 catalyst showed a little loss of its activity (7% for the FAL and 4% for the AL).